Integrated transcriptomic and metabolomic analysis reveals the effects of forchlorfenuron and thidiazuron on flavonoid biosynthesis in table grape skins - Ting Zheng; Pengcheng Zhao; Jiang Xiang; Lingzhu Wei; Wanting Shen; Jiang Wu; Jianhui Cheng (Current Plant Biology)
Forchlorfenuron (CPPU) and thidiazuron (TDZ) are the most commonly used plant growth regulators in grape production. However, their application can result in astringency and uneven fruit skin coloring, which are related to flavonoid metabolic pathway. Therefore, this study investigated the effects of CPPU and TDZ on flavonoid synthesis in ‘Tiangong Moyu’ grape. The swelling effect of TDZ was better than that of CPPU, with T5 (25 mg·L−1 GA3+2.5 mg·L−1 TDZ applied at 100 % flowering and 25 mg·L−1 GA3+2.5 mg·L−1 TDZ applied 15 d later) showing the best swelling effect. Both CPPU and TDZ increased flavonoid content, and CPPU accelerated coloring. Combined with transcriptome analysis, cluster analysis showed that treatments T3 (two CPPU applications) and T5 had the strongest correlation. T5 caused the greatest change in flavonoid biosynthesis pathway. Weighted gene co-expression network analysis (WGCNA) showed that MM.magenta was correlated with tannin and flavonoid contents. GST23 was consistent with the mature fruit flavonoid contents. WRKY57 and MYB86 increased after CPPU and TDZ treatment, especially in T5. Metabolomic analysis showed that the smallest difference in composition occurred between T1 (control) and T4 (one TDZ application), and naringenin only showed differences in T1 vs T4 and T1 vs T5, with enrichment in the flavonoid biosynthesis pathway. Association analysis in the flavonoid synthesis pathway showed that catechin, dihydrokaempferol, and naringenin were associated. Catechin is closely related to CHS17, with higher levels in T2 (one CPPU application) and T3. The above results provide a theoretical basis for improving grape berry quality using plant growth regulators.